Prologue to the Symposium Quality in obstetrical care - Santivañez Pimentel, Alvaro Cesar (2019)
Avedis Donabedian developed the unique task of adapting quality approaches to health services. In his proposal, he placed patient safety in the core of quality management. The Ibero-American study of adverse events IBEAS demonstrated that one of the specialties where we need to address patient safety is obstetrics and gynecology. Peru was one of the first countries in Latin America to develop national proposals on patient safety. This symposium aims to present the national experience in the implementation of patient safety in obstetrical care.